An Investigation into the use of floating-tip ailerons on skew-wing aircraft - Davis, Robert Jocelyn (My University, 2015)
Wind-tunnel tests were conducted on a rectangular platform skew wing, fitted with floating-tip ailerons. Rolling criteria calculated from static rolling moment and lift results showed good aileron performance in the low incidence cruise regime. Trends were for favourable yawing moments to be generated; the usual asymmetric pitch/roll cross-coupling was observed. Rolling performance in the unskewed position was reasonably well predicted by lifting-line theory - the resulting lift distribution appeared very non-elliptic towards the wing-tips, resulting in higher induced drag than the optimum elliptic distribution. Tests on a second wind-tunnel model indicated that the effect of the incidence discontinuity at the wing/aileron interface spread further span wise chan was expected. Conclusions were that the improved roll performance of floating-tip ailerons might be outweighed by the increase in induced drag. Further research was required in the transonic regime to determine effects on wave drag. Research into the dynamic performance was also required. It is suggested that lifting-surface theory be used for performance prediction of the skewed case.